1992
DOI: 10.1056/nejm199201163260304
|View full text |Cite
|
Sign up to set email alerts
|

Improved Light-Microscopical Detection of Microsporidia Spores in Stool and Duodenal Aspirates

Abstract: E. bieneusi is an important cause of chronic diarrhea in HIV-infected persons. This new diagnostic technique serves as a practical, noninvasive means to detect microsporidia spores in stool specimens and is also applicable to the examination of duodenal aspirates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
305
1
13

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 464 publications
(324 citation statements)
references
References 29 publications
5
305
1
13
Order By: Relevance
“…The fresh fecal samples were first processed by the Baermann (1917) method. After that, the samples were preserved in 10% formalin and processed by the Lutz (1919) and Ritchie (1948) methods and the Safranin/Methylene Blue (Baxby et al 1984) and Weber's chromotrope modified Trichrome (Weber et al 1992) staining techniques. All samples were submitted to the five parasitological methods cited above.…”
mentioning
confidence: 99%
“…The fresh fecal samples were first processed by the Baermann (1917) method. After that, the samples were preserved in 10% formalin and processed by the Lutz (1919) and Ritchie (1948) methods and the Safranin/Methylene Blue (Baxby et al 1984) and Weber's chromotrope modified Trichrome (Weber et al 1992) staining techniques. All samples were submitted to the five parasitological methods cited above.…”
mentioning
confidence: 99%
“…The microsporidian protozoan organism Enterocytozoon bieneusi, first reported in 1985 [1,2], has been recognized as a human immunodeficiency virus (HIV)-associated intestinal opportunistic pathogen [1][2][3][4][5][6][7][8][9]. Preliminary epidemiological studies have indicated that it may be present in 10%-30% of severely immunodeficient HIV-infected adults with chronic diarrhea [3][4][5][6]9].…”
mentioning
confidence: 99%
“…In summary, mean ages were similar for both groups. Weight loss and cachexia were significantly more important in patients with microsporidiosis, either 303 staining, or the new gram-chromotrope were sufficient to establish a diagnosis 27,37 . Besides reducing the necessity of invasive procedures, it has special interest in developing countries such as Brazil, since the costs of more sophisticated methods like biopsy or PCR were reduced as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our negative findings using these methods in specimens from two patients in whom microsporidia spores were detected in stool samples using either light microscopy or PCR, suggests that tissue examination using LM may also fail to detect microsporidia in small-bowel tissue. The variable sensitivity of LM may be due to the focal distribution of infected enterocytes, the selected biopsy site, the small amount of tissue obtained with biopsies or the lack of utilization of Warthin-Starry or Gram-chromothrope, more specific stainning for microsporidia in tissues 17,28,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation